PENGEMBANGAN POLA TANAM DAN DIVERSIFIKASI TANAMAN PANGAN DI MADURA : SUATU UPAYA PENINGKATAN PRODUKSI DAN PENDAPATAN PETANI - R.A. Sidqi Zaed Z.M.; Firman Farid Muhsoni; Achmad Amzeri; Fuad Hasan (Agrovigor, 2010)
Crop patern in the rainy season caused unutilization land in Madura.this purpose research is agroecosystem agriculture map using remote sensing, cropp development models by agroecosystem. Method research with site selection to use agriculture plants with maching between land quality in mapping unit and evaluation food plants. Output this research is potential agriculture map for corn cultivation, wide area very appropriate 70,279.5 ha (15,4%), appropriate 211,512.3 ha (46,3%). Rice plant potential appropriate 209,769 ha (46%), very appropriate 33,699 ha (7,4%). Wide soybean potential appropriate 162,618 ha (35,6%), very appropriate 25,091 ha (5,5%). Wide tobacco potential appropriate 51,971ha (11,4%) and very appropriate 8,749ha (1,9%). Wide peanut potential appropriate 192,312ha (42,1%). very appropriate 19,474ha (4,3%). Agricultura development in Madura for soybean is baluran variety with production 2.200 kg/ha and grow during 75 day, peanut is Kamal variety with production 2.500 kg/ha and grow during 86 day. Corn for paddyfield is tambin variety production 3.840 kg/ha and grow during 73 day, for dry land is mading variety with production 2.380 kg/ha (62 day). Rice plant is PD3 variety with grow during 100 day ang production 2.400 kg/ha, for irrigation land is PD4 variety with production 2.400 kg/ha and grow during 108 day. Wide tobacco is jepon kenik variety with grow during 86 day and plants index high (580)